Pharmacodynamic Profiles of Dual-Pathway Inhibition with or without Clopidogrel versus Dual Antiplatelet Therapy in Patients with Atherosclerotic Disease - Galli, Mattia; Franchi, Francesco; Rollini, Fabiana; Been, Latonya; Jaoude, Patrick Abou; Rivas, Andrea; Zhou, Xuan; Jia, Sida; Maaliki, Naji; Lee, Chang Hoon; Pineda, Andres M.; Suryadevara, Siva; Soffer, Daniel; Zenni, Martin M.; Geisler, Tobias; Jennings, Lisa K.; Bass, Theodore A.; Angiolillo, Dominick J. (Thrombosis and Haemostasis, 2022)
Aim Inhibition of thrombin-mediated signaling processes using a vascular dose of rivaroxaban in adjunct to antiplatelet therapy, known as dual-pathway inhibition (DPI), reduces atherothrombotic events in patients with stable atherosclerotic disease. However, there are limited data on the pharmacodynamic (PD) effects of this strategy and how it compares to standard dual antiplatelet therapy (DAPT).Methods and Results This investigation was conducted in selected cohorts of patients (n = 40) with stable atherosclerotic disease—enrolled within a larger prospective, open-label, parallel-group PD study—who were treated with either aspirin plus clopidogrel (DAPT), aspirin plus rivaroxaban 2.5 mg/bid (DPI), or DAPT plus rivaroxaban 2.5 mg/bid. Multiple PD assays providing a comprehensive assessment of markers of thrombosis were used. PD endpoints included platelet-mediated global thrombogenicity measured by light transmittance aggregometry (LTA) following stimuli with CATF (collagen-related peptide + adenosine diphosphate [ADP] + tissue factor [TF]), markers of P2Y12 reactivity, markers of platelet aggregation using LTA following several stimuli (arachidonic acid, ADP, collagen, TF, and thrombin receptor-activating peptide [TRAP]), thrombin generation, and thrombus formation. There was no difference in platelet-mediated global thrombogenicity between groups. Rivaroxaban significantly reduced thrombin generation and was associated with a trend toward reduced TF-induced platelet aggregation. Clopidogrel-based treatments reduced markers of P2Y12 signaling and TRAP-induced platelet aggregation. There were no differences between groups on markers of cyclooxygenase-1-mediated activity.Conclusion Compared with DAPT, DPI does not result in any differences in platelet-mediated global thrombogenicity, but reduces thrombin generation. These PD observations suggest that modulating thrombin generation—by means of factor Xa inhibition—in adjunct to antiplatelet therapy provides effective antithrombotic effects, supporting the efficacy and safety findings of a DPI strategy observed in clinical trials.
Keywords: rivaroxaban; dual-pathway inhibition; dual antiplatelet therapy; atherosclerotic disease; clopidogrel; aspirin; pharmacodynamic